Ephemeral spectacles, exhibition spaces and museums 1750-1918 - Bauer, Dominique; Murgia, Camilla 1977- (Spatial Imageries in Historical Perspective, 2021)
Cover -- Table of Contents -- Introduction: Staging the Temporary: The Fragile Character of Space -- Camilla Murgia -- I: The Department Store -- 1. "One Need Be Neither a Shopper Nor a Purchaser to Enjoy:" Ephemeral Exhibitions at Tiffany &amp -- Co., 1870-1905 -- Amy McHugh and Cristina Vignone -- 2. Enclosed Exhibitions: Claustrophobia, Balloons, and the Department Store in Zola's Au Bonheur des Dames -- Kathryn A. Haklin -- II: Spectacles -- 3. Jardins-Spectacles: Spaces and Traces of Embodiment -- Susan Taylor-Leduc -- 4. Parading the Temporary: Cosmoramas, Panoramas, and Spectacles in Early Nineteenth-Century Paris -- Camilla Murgia -- 5. Portable Museums: Imaging and Staging the "Northern Gothic Art Tour" - Ephemera and Alterity -- Juliet Simpson -- III: At the Intersection of Literature and the Built Environment -- 6. The Elusiveness of History and the Ephemerality of Display in Nineteenth-Century France and Belgium: At the Intersection of the Built Environment and the Spatial Image in Literature -- Dominique Bauer -- 7. The "Phantasmatic" Chinatown in Helen Hunt Jackson's "The Chinese Empire" and Mark Twain's Roughing It -- Li-hsin Hsu -- IV: The Museum and Alternative Exhibition Spaces -- 8. "Show Meets Science:" How Hagenbeck's "Human Zoos" Inspired Ethnographic Science and Its Museum Presentation -- Stefanie Jovanovic-Kruspel -- 9. The Last Wunderkammer: Curiosities in Private Collections between the Nineteenth and Twentieth Centuries -- Emanuele Pellegrini -- 10. The Impact of Alternative Exhibition Spaces on European Modern Art before World War I -- Nirmalie Alexandra Mulloli -- Index.